An investigation of structure-function relations in articular cartilage during skeletal maturation - Gannon, Alanna (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
The over-riding objective of this thesis was to build upon our current understanding of the evolving nature of articular cartilage mechanics by elucidating how changes to structure and composition of the tissue during postnatal development and maturation impact the depth dependent compressive mechanical properties of the tissue.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin.